A Friend virus mutant encodes a small glycoprotein that causes erythroleukemia. - Hoatlin, M E (1994)
The Pvu delta mutant of Friend spleen focus-forming virus encodes the smallest env glycoprotein (apparent M(r), 41,000) known to activate erythropoietin receptors. In vivo, Pvu delta causes erythroblastosis and the development of erythroleukemia. We isolated two leukemic cell lines that contain Pvu delta; both synthesize hemoglobin in response to dimethyl sulfoxide. The Pvu delta env gene contains a 204-base deletion in the ecotropic-specific region, suggesting that this domain of the glycoprotein is not essential for viral pathogenesis.